PENYUSUNAN LAPORAN KEUANGAN UMKM BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL MENENGAH PADA KM ALUMINIUM - Fitri Iman Sari fitri; Alia Ariesanti (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The preparation of financial statements according to standards is needed to provide information about the performance of the entity for internal and external users. However, there are still many EMKMs that have not prepared financial reports according to SAK EMKM, one of which is KM Alumunium which is engaged in industry and produces various products made of aluminum in Kranon Hamlet, Sorosutan. This service activity aims to provide an understanding of the process of preparing financial reports and assistance in preparing financial reports per SAK EMKM. Service activities are carried out at partner locations. The results of this service activity are that partners gain knowledge about the process of preparing financial reporting, and partners have financial reports that are by EMKM standards.